Biorational insecticide against corn rootworm in Durango - Flores-Villegas, Mónica Yazmín; Ordaz-Díaz, Luis Alberto; Madrid-Del Palacio, Maribel; García-Gutiérrez, Cipriano; Zazueta-Álvarez, David Enrique; Bailón-Salas, Ana María (Revista Mexicana de Ciencias Agrícolas, 2022)
Agriculture in Mexico has surpassed the rational use of chemical insecticides, thereby impacting soil structure and the agricultural ecosystem in general. A pest control alternative is the use of toxic plants, which provide chemicals that modify the behavior of insects. The objective of this research was to evaluate the efficacy of a biorational insecticide generated with Datura metel Linnaeus applied on adult populations of the corn rootworm Diabrotica undecimpunctata Howardi during the 2019 spring-summer cycle, in Durango. One thousand six hundred twenty individuals were evaluated at different doses 10, 20, 50 and 70 mg L-1 every 0, 2, 4, 6, 8, 10, 12 and 24 h. In addition, the values of LD50 and the 95% confidence interval were determined for each treatment. The doses evaluated caused the mortality of corn rootworm, which varied depending on the dose and structure analyzed. The LD50 calculated for the root was 23.2 mg L-1, for the leaf 34.1 mg L-1 and for the stem 89.3 mg L-1. By increasing the dose to 70 mg L-1 of root, it was possible to achieve a mortality of 76%, so it is concluded that there is a directly proportional relationship between the structure evaluated and the dose applied to adults of corn rootworm and the time of exposure.